Performance analysis of optimized VANET protocols in real world tests - Toutouh-El-Alamin, Jamal; Alba-Torres, Enrique (IEEE, 2011)
Vehicular ad hoc networks (VANETs) provide the communications required to deploy Intelligent Transportation Systems (ITS). In the current state of the art in this field there is a lack of studies on real outdoor experiments to validate the new VANETs protocols and applications proposed by designers. In this work we have addressed the definition of a testbed in order to study the performance of the Vehicular Data Transfer Protocol (VDTP) in a real urban VANET. The VDTP protocol has been tested by employing six different parameter settings: one defined by human experts and five automatically optimized by means of metaheuristic algorithms (PSO, DE, GA, ES, and SA). As a result, we have been able to confirm the performance improvements when optimized VDTP configurations are used, validating the results previously obtained through simulation.
Performance Analysis of Optimized VANET Protocols in Real World Tests
Keywords: Sistemas de transporte inteligente; Protocolos de comunicaciones; Vehicular ad hoc networks